Underestimated latent tuberculosis infection burden among school contacts in China: a cross-sectional study - Jin Yin; Mei Wang; Chengguo Wu; Yaling Shi; Ying Liu; Ya Yu; Qian Su; Zhengyu Zhang; Xueyong Huang; Xiaoshuang Zhang; Jun Fan; Bo Wu (Archives of Public Health)
Abstract Background Previous research has indicated a low tuberculin skin tests (TST) strong positive rate in school tuberculosis (TB) screening implemented by community-level medical and health care institutions in China. The research objective was to evaluate the latent tuberculosis infection (LTBI) detection gap in school contact investigation in China. Methods In this cross-sectional study, school contacts were investigated by Chongqing Municipal Institute of Tuberculosis between January 2022 and April 2024 in Chongqing, China. TST, creation tuberculin skin test (C-TST), or Interferon-gamma release assays (IGRA) were conducted for immunological diagnostic methods. The LTBI detection gap among school contacts was assessed by comparing with the data implemented by community-level medical and health care institutions from 2021 to 2022. Results In 6063 participants, 4233 were tested using TST, 1799 were tested using C-TST, and 31 were tested using IGRA. Seven students were confirmed to have active TB. The LTBI prevalence rate using TST and C-TST was 15.2% (95%CI, 14.1-16.3%) and 3.6% (95%CI, 2.7-4.4%) respectively. A LTBI detection gap of 10.3% was identified when comparing with TST results implemented by community-level medical and health care institutions (χ 2 = 636, P < 0.001). Conclusions TB school contact investigation plays an important role in controlling TB epidemic. However, there may be a LTBI detection gap, likely due to poor quality control of TST implemented by community-level medical and health care institutions.